2013
DOI: 10.1002/embr.201337642
|View full text |Cite
|
Sign up to set email alerts
|

Extensive regulation of the non‐coding transcriptome by hypoxia: role of HIF in releasing paused RNA pol2

Abstract: Hypoxia is central to both ischaemic and neoplastic diseases. However, the non-coding transcriptional response to hypoxia is largely uncharacterized. We undertook integrated genomic analyses of both non-coding and coding transcripts using massively parallel sequencing and interfaced this data with pan-genomic analyses of hypoxia-inducible factor (HIF) and RNApol2 binding in hypoxic cells. These analyses revealed that all classes of RNA are profoundly regulated by hypoxia and implicated HIF as a major direct re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
187
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(198 citation statements)
references
References 23 publications
11
187
0
Order By: Relevance
“…Although we did not observe changes in the expression of EMT transcription factors in our data sets, it is possible that Malat1 expression could increase in cells that are undergoing EMT, and that may correlate well with those cells preferentially metastasizing. In this context, it has been shown previously that hypoxia-inducible factor HIF1A regulates MALAT1 expression (Choudhry et al 2014;Michalik et al 2014). Hif1a is a major transcription factor that governs oxidative stress and regulates tumor progression and has also been shown to play a role in EMT (Semenza et al 2003).…”
Section: Malat1 Level Increases Upon Cancer Progressionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although we did not observe changes in the expression of EMT transcription factors in our data sets, it is possible that Malat1 expression could increase in cells that are undergoing EMT, and that may correlate well with those cells preferentially metastasizing. In this context, it has been shown previously that hypoxia-inducible factor HIF1A regulates MALAT1 expression (Choudhry et al 2014;Michalik et al 2014). Hif1a is a major transcription factor that governs oxidative stress and regulates tumor progression and has also been shown to play a role in EMT (Semenza et al 2003).…”
Section: Malat1 Level Increases Upon Cancer Progressionmentioning
confidence: 93%
“…Hif1a is a major transcription factor that governs oxidative stress and regulates tumor progression and has also been shown to play a role in EMT (Semenza et al 2003). In a number of cell culture studies, Malat1 was found to be up-regulated upon stress such as serum starvation, hypoxia, and genotoxic stress, all of which are linked to tumor progression (Yang et al 2011;Mizutani et al 2012;Choudhry et al 2014). Consistent with this, our findings demonstrated that Malat1 loss in dedifferentiated primary tumors results in extensive alteration in gene expression, activating pathways that are involved in morphogenesis and differentiation.…”
Section: Malat1 Level Increases Upon Cancer Progressionmentioning
confidence: 99%
“…Hypoxia is a major physiological difference between normal and tumour tissues [4], associated with worse patient survival and chemotherapy [5] and radiotherapy resistance [6]. Hypoxia stabilises the transcription factors, hypoxia inducible factors, HIF1α and HIF2α, which dramatically change the hypoxic cell transcriptome as a key response to the hypoxic insult [2]. This triggers more aggressive tumour growth, survival, invasion and metastasis and increases the stem cell component of tumours through HIF1α and HIF2α regulated genes [7].…”
Section: Introductionmentioning
confidence: 98%
“…Normal tissues have an oxygen level of pO 2 9 mmHg-pO 2 100 mmHg (1.2-13 % O 2 ) [1]. Hypoxia is an environmental stress induced in many pathological settings including wound healing, inflammation, ischemia and cancer [2]. Hypoxic regions of tumours are caused by high metabolic and proliferative rates and poor tumour vascularisation [3].…”
Section: Introductionmentioning
confidence: 99%
“…ChIP-seq data from MCF-7 breast adenocarcinoma cells were obtained from publicly available data sets (accession numbers: GSE28352 and E-MTAB-1995) as described previously [12,39]. Chromatin immunoprecipitations (ChIP) and FAIRE assays were performed as described previously [40] using antibodies against HIF-1α (Cayman Chemicals, Cay10006421), HIF-1β (Novus Biologicals, NB100-110) and RNA polymerase II (Santa Cruz, SC-899).…”
Section: Chromatin Immunoprecipitations and Faire Assaymentioning
confidence: 99%